THE EFFECT OF MANAGERIAL OWNERSHIP, FINANCIAL PERFORMANCE, AND FIRM SIZE TO SOCIAL RESPONSIBILITY (CSR) DISCLOSURE OF MANUFACTURING COMPANY TO GO PUBLIC IN INDONESIA STOCK EXCHANGE FOR THE PERIOD OF 2007–2009 - Meta Fidiana; Susi Handayani (Universitas Negeri Malang, 2015)
The high level of public awareness as the impact of environmental degradation and pressurefrom stakeholders regarding the development of the business world, it creates new awareness about theimportance of implementing corporate social responsibility (CSR) in the company. One of the way tocommunicate and interact with stakeholders is by disclose corporate social responsibility which isreported in the company’s annual report. Corporate social responsibility disclosure is affected bymanagerial ownership, financial performance, and firm size. The purpose of this study is to examine andto analyze the influence of managerial ownership, financial performance, and firm size on corporatesocial responsibility (CSR) disclosure manufacturing company that go public on the Indonesia StockExchange 2007–2009. This study applies purposive sampling method to take samples, so that it obtainsnumbers of 19 manufacture companies. The method of analysis is applied multiple linear regressionanalysis with the help of analysis tools SPSS version 16. Based on the results of data analysis can beconcluded that there is a simultaneous effect among managerial ownership, financial performance, andfirm size on corporate social responsibility (CSR) disclosure. While partial, financial performance, andfirm size have a significant influence on the of corporate social responsibility (CSR) disclosure. Whereasmanagerial ownership has no significant effect on the corporate social responsibility (CSR) disclosure.Keywords:Corporate Social Responsibility (CSR), managerial ownership, financial performance, firmsize, corporate manufacturing